A Case Report on Ayurvedic Management of Vicharchika (Eczema): A Sustainable Alternative to Corticosteroid Treatment - Farhan, Mohammed; Maksane, Sushant; Bansal, Priyal; Borkar, Preeti (Journal of Neonatal Surgery, 2025)
Background: All diseases of the skin have been classified under the Kushta (Skin Disease) categories in Ayurveda. Vicharchika is one of them. This is a kaphadosha predominance tridoshajvyadhi. This case demonstrates the successful treatment of Vicharchika (Eczema) with comprehensive ayurvedic treatment offering holistic treatment and improve overall well being. It shows symptoms like clear fluid oozing (strava), pain (ruja), itching (kandu) and bump (utseda). It can be correlated with the Eczema in contemporary science. In Ayurveda Vicharchika (Eczema) is a type of kshudra (small) Kushta (Skin disease). Case: a case of 28 year old male patient presented with intense itching and dry lesions with bumps on the posterior part of neck, and having pulling sensation while in contact with water for 6 months. Management: Arogyavardhinivati (Ayurvedic formulation), Manjistha (Rubia cordifolia) and Haridra (Curcuma longa) churnalepa–Gharshan (past application and dry powder rubbing) and Rakt-Prasadan karma (Paste for improvement of blood tissue quality). Ras-Rakt-pachak-kwath (A Decoction for enhancing blood tissue quality), Sarivaarishta, Jalokaavcharan(Leech therapy) and Takradhara (Buttermilk Stream) Conclusion: Vicharchika can be included as Eczema. All types of skin diseases are under the umbrella of Kushtha in Ayurveda. It requires long term treatment in both forms suppressive and systemic. This case highlights the ayurvedic management of Vicharchika (Eczema), providing sustainable relief while enhancing the well being, Arogyavardhini, saarivasava and other treatments provide effective alternative to corticosteroid cream in treatment of Vicharchika,